Multi-centred Mixed-methods PEPFAR HIV Care & Support Public Health Evaluation: study protocol - Harding, Richard; Simms, Victoria; Penfold, Suzanne; Mwangi-Powell, Faith; Namisango, Eve; Higginson, Irene J. (BMC Public Health, 2010)
A public health response is essential to meet the multidimensional needs of patients and families affected by HIV disease in sub-Saharan Africa. In order to appraise curret provision of HIV care and support in East Africa, and to provide evidence-based direction to future care programming, and Public Health Evaluation was commissioned by the PEPFAR programme of the US Government.This paper described the 2-Phase international mixed methods study protocol utilising longitudinal outcome measurement, surveys, patient and family qualitative interviews and focus groups, staff qualitative interviews, health economics and document analysis.To describe the nature and scope of HIV care and support in two African countries, including the types of facilities available, clients seen, and availability of specific components of care [Study Phase 1]. Aim 2) To determine patient health outcomes over time and principle cost drivers [Study Phase 2].The study objectives are as follows. 1) To undertake a cross-sectional survey of service configuration and activity by sampling 10% of the facilities being funded by PEPFAR to provide HIV care and support in Kenya and Uganda (Phase 1) in order to describe care currently provided, including pharmacy drug reviews to determine availability and supply of essential drugs in HIV management. 2) To conduct patient focus group discussions at each of these (Phase 1) to determine care received. 3) To undertake a longitudinal prospective study of 1200 patients who are newly diagnosed with HIV or patients with HIV who present with a new problem attending PEPFAR care and support services. Data collection includes self-reported quality of life, core palliative outcomes and components of care received (Phase 2). 4) To conduct qualitative interviews with staff, patients and carers in order to explore and understand service issues and care provision in more depth (Phase 2). 5) To undertake document analysis to appraise the clinical care procedures at each facility (Phase 2). 6) To determine principle cost drivers including staff, overhead and laboratory costs (Phase 2).
Keywords: Spiritual Care, Data Collection Tool, Focus Group Discussion, Mental Health Score, United States Government